Mental health assessment among hypermarket workers in shopping mall - Hazreel Hazimi, Hisyamuddin (2025)
The demanding nature of hypermarket jobs has significantly contributed to the rise in work-related stress and mental health challenges among employees. This study examines the interconnected factors influencing job satisfaction, stress levels, and the sociodemographic characteristics of hypermarket workers through structured questionnaires, collecting data on stress levels, physical demands, working hours, and managerial support. The findings reveal that heavy workloads, prolonged hours, and inadequate managerial support are the primary drivers of elevated stress and dissatisfaction. To address these issues, the study recommends targeted interventions such as stress management training programs to help employees cope with workplace pressures, ergonomic improvements to reduce physical strain, and enhanced communication between management and employees to foster a supportive and inclusive environment. These strategies aim to improve employee mental well-being, promote healthier and more productive workspaces, reduce turnover, and ensure a sustainable workforce in the competitive retail industry.